(untitled) (Journal of the College of Basic Education, 2024)
Concentrations of 25, 50, 100, 200 and 300 mg of nano-encapsulated and non-encapsulated Alpha-Linolenic Acid (ALA) were used to enrich 1 kg of manufactured cream. The treatments to which encapsulated ALA was added were less susceptible to the oxidation process than the treatments to which ALA non-encapsulated was added. The Poly Lactic Acid (PLA) coating had a major role in protecting ALA by forming a protective layer that protects this acid from the action and activity of lipase enzymes. Adding encapsulated ALA to cream limited microbial growth in it. The results of the sensory evaluation indicated that Treatment C1 obtained the highest average score for the characteristics of taste, flavor, texture characteristics, color, appearance, and spreadability, which were 37, 27, 13, and 8 degrees, respectively, at the end of the storage period. Thus, it had the highest total score among all other cream treatments, which is 85 degrees. In contrast, it was found that the lowest Total scores of 39 and 48 were obtained by treatments C10 and C9, which indicates that encapsulating ALA and adding it to the cream helped preserve it for a longer period without affecting its various characteristics.